2019
DOI: 10.1088/2057-1976/ab2307
|View full text |Cite
|
Sign up to set email alerts
|

A micro-fabricated in vitro complex neuronal circuit platform

Abstract: Developments in micro-manufacture as well as biofabrication technologies are driving our ability to create complex tissue models such as ‘ organ-on-a-chip ’ devices. The complexity of neural tissue, however, requires precisely specific cellular connectivity across many neuronal populations, and thus there have been limited reports of complex ‘ brain-on-a-chip ’ technologies modelling specific cellular circuit function. Here we describe the development of a model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…There are several ways in which these ideas may be implemented, however, in the short term it appears that the use of fluidic chambers and tunnels may provide the most robust, reliable and durable assays using current technology. Dr Roach and his group are currently fabricating platforms enabling the segregated co-culture of neurons to be controlled, with connectivity between neuronal populations being possible only by direction of neurites through microchannels [Kamudzandu, 2019]. Such devices are becoming more commonplace in the literature, although very few address the issues of multiple different neuronal types within a single device.…”
Section: Discussionmentioning
confidence: 99%
“…There are several ways in which these ideas may be implemented, however, in the short term it appears that the use of fluidic chambers and tunnels may provide the most robust, reliable and durable assays using current technology. Dr Roach and his group are currently fabricating platforms enabling the segregated co-culture of neurons to be controlled, with connectivity between neuronal populations being possible only by direction of neurites through microchannels [Kamudzandu, 2019]. Such devices are becoming more commonplace in the literature, although very few address the issues of multiple different neuronal types within a single device.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in vitro models where different cell populations can be grown and connected “ad hoc” present simplified but valuable tools to investigate network function as well as neuropathological conditions. Microfluidic technologies have been employed to create human brain‐mimicking neuronal circuits for the study of cortico‐striatal networks using calcium imaging (Lassus et al., 2018), to model neuroprotective mechanisms (Samson et al., 2016), to study structure–function relationship by precise neurite guidance achieved by electric fields [77]), to highlight brain region‐specific cell identities (Kamudzandu et al., 2019), physiology and function (Dauth et al., 2017), to create 3D structured circuits (van de Wijdeven et al., 2018) and for drug screening (S. R. Lee et al., 2019) (Figure 3). Kajtez et al, have also recently used a hybrid fabrication technique by integrating 3D printing with soft lithography to provide rapid prototyping at both micro‐ and macroscale, enabling open‐well compartmentalized devices with greater freedom of device design (Figure 3a) (Kajtez et al, 2020).…”
Section: Microfluidic Tools To Study Neuronal Functionmentioning
confidence: 99%
“…Similarly Hernández et al, used glutamate‐induced excitotoxicity in a compartmentalized microfluidic neuronal circuit to study axonal degeneration, showing co‐activation of two independent degenerative mechanisms in axon and soma, with axonal degeneration progressing via necroptotic kinases RIPK1 and RIPK3, while apoptotic events predominate in the soma (Hernandez et al., 2018). The use of microfluidic neuronal circuits consisting of multiple neuronal types, such as that presented by Kamudzandu et al which mimics the circuitry of the basal ganglia, may further shed light on the influence of excitotoxity on network activity (Kamudzandu et al., 2019).…”
Section: Microfluidic Models Of Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in microfluidics and micropatterning have shown that constrictive funnel motifs may be employed to gate directional neurite extension. 29,[63][64][65] Building upon these findings, we used 2PP to fabricate a matrix of 2.5D triangles in a repeated pattern, with the aim of guiding directional neurite extension over relatively large distances (>500 μm). Progenitors cultured upon patterned and planar unpatterned platforms were synchronously differentiated and analysed to determine their distribution and orientation (Fig.…”
Section: Guidance Of Neuronal Processes By 2pp Generated Microstructuresmentioning
confidence: 99%